2017
DOI: 10.3390/toxins9080239
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Mechanisms Involved in Strong Hemorrhage and Dermonecrosis Induced by Atroxlysin-Ia, a PI-Class Snake Venom Metalloproteinase

Abstract: Hemorrhage is the most prominent effect of snake venom metalloproteinases (SVMPs) in human envenomation. The capillary injury is a multifactorial effect caused by hydrolysis of the components of the basement membrane (BM). The PI and PIII classes of SVMPs are abundant in viperid venoms and hydrolyze BM components. However, hemorrhage is associated mostly with PIII-class SVMPs that contain non-catalytic domains responsible for the binding of SVMPs to BM proteins, facilitating enzyme accumulation in the tissue a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 59 publications
1
26
0
1
Order By: Relevance
“…Escalante et al [28] demonstrated the extensive hydrolysis of laminin α and γ chains by BaPI (PI-class) and in the case of Jararhagin (PIII-class) by most of hydrolysis was of the nidogen and only the α-chain of laminin. In in vivo experiments, Freitas-De-Sousa et al [20] observed that ATXL and BATXH degraded collagen IV and laminin, with total collagen digestion by ATXL, which would explain the proteinase ability to induce hemorrhage, since these BM components play important role in the stability of capillaries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Escalante et al [28] demonstrated the extensive hydrolysis of laminin α and γ chains by BaPI (PI-class) and in the case of Jararhagin (PIII-class) by most of hydrolysis was of the nidogen and only the α-chain of laminin. In in vivo experiments, Freitas-De-Sousa et al [20] observed that ATXL and BATXH degraded collagen IV and laminin, with total collagen digestion by ATXL, which would explain the proteinase ability to induce hemorrhage, since these BM components play important role in the stability of capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…The differences among doses from 1 to 5 μg, within and between each toxin group, were not statistically significant, indicating that the two-times-lower molecular mass of ATXL than BATXH would not impact the comparisons in this range of doses. The intermediate dose of 2 μg/mouse was then selected to evaluate and compare the time course of the edema induced by both toxins, since this dose was capable of inducing edema without causing hemorrhage in the animals [20]. Mice (n = 6) were injected on the left paw with different protein doses (0.5, 1, 2 and 5 μg/animal) or with saline as negative control.…”
Section: Inflammatory Reaction Induced By Svmpsmentioning
confidence: 99%
See 3 more Smart Citations